Microwave Processing at 915 MHz for Efficient Cellulose Cleavage in Vegetable Wastewater Treatment - Gonzalez Z., Melissa F. (Zamorano: Escuela Agrícola Panamericana, 2025)
Wastewater treatment is crucial for protecting both the environment and public health by removing contaminants before discharge. In the pursuit of environmental sustainability, interest in advanced technologies to optimize industrial wastewater management has grown. This study evaluated the effects of microwave processing at a frequency of 915 MHz on vegetable wastewater, focusing on cellulose cleavage by breaking ?-1,4-glycosidic bonds, due to the environmental impact this polysaccharide has on wastewater from the fruit and vegetable processing industry. Parameters such as pH, viscosity, density, cellulase activity, and concentrations of glucose and organic acids were analyzed. The results indicated that as the MW treatment power increased, there was a significant rise in glucose concentration, which could increase up to twelve-fold, along with cellulase activity, which could increase too eightfold. Additionally, butyric acid levels doubled in the treated wastewater. A notable reduction in pH and density also occurred with higher power application. However, other parameters, such as viscosity and concentrations of acetic, formic, and propionic acids, remained unchanged despite the increase in treatment power. Therefore, the potential of MW technology was highlighted as an effective solution for wastewater treatment in the horticultural processing industry, aiming to prevent water quality degradation by enhancing the efficiency of organic contaminant removal, ensuring regulatory compliance, and reducing regulatory risks associated with wastewater discharge.